Absenteeism and associated factors: a study addressing the workers from a footwear manufacturer - Daniela Inês Thier Roloff; Clarice Alves Bonow; Daiani Modernel Xavier; Mara Regina Santos da Silva; Adriane Maria Netto de Oliveira; Marta Regina Cezar-Vaz (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objectives: To characterize absenteeism among the workers of a footwear manufacturer and analyze associated factors. Method: This quantitative and cross-sectional study addressed 572 workers from a footwear company located in southern Brazil, totaling 1,902 sick leaves in 2017. Analyses considered absolute and relative frequencies, and univariate and multivariate Poisson regression models were performed. Results: Most workers taking a leave from work were women with a job position in the operational sector to accompany a family member to attend a medical appointment or take exams. In the multivariate analysis, the following variables appeared associated with leaves longer than three days: being ≥ 50 years older, working in the Production Support sector, working in the company from 16 to 20 years, and nine groups of diseases (ICD-10). Conclusion: The findings contribute to understanding this industry's absenteeism profile, supporting strategies to promote positive economic and social impact, and promote adequate occupational health and safety.